Pravda kao težište ravnoteže pozitivnog prava / Justice as the Balance Center of Gravity of Positive Law - Alibašić, Mirnes (Pregled: časopis za društvena pitanja / Periodical for social issues, 2014)
In this paper, we discuss the concept, the essence and the balance of justice and positive law. This paper is divided into three parts. The first part of the paper is actualized idea of law and essential justice in society. In that section is presented an introduction of the problem, determined by the research. The second part analyzes the development of the positive law’s elements. Logically coherent and relying on the previous text, the third part of the paper deals with the problem of balancing justice and rights. Here is given a broader spectrum of balanc¸ing justice and positive law by researching, analyzing and considering social relations on the the principles of justice. The interdisciplinary approach is used to set the focal point of relations balance rights, of emphasis balance right. The first two sections of paper are having an accent on historical and empirical analyses about justice and law. In some different way, third section is initiated to the question of balance about justice and law. On the pillars of these facts, we have considered the wide spectrum of balance and relation between justice and positive law. In addition, we are perceived a rule between justice relationship and justice society relationship. On the application of branch of knowledge, we put down the key point about relation in justice of law, which was determined by the balance of law. The continuing of this paper are presenting some ways about derange of system balance inside the law. In the specific way of justice, as are (balance between justice and positive law, interest as a fund for center of balance between positive and natural law, justice as a center of balance between positive law and human rights and freedom) what is based on the basic thesis which is assertion of justice as a center of gravity balance of positive law. In conclusion, on systematic way we have presented synthesis of all relevant knowledge about justice and positive law that have been discussed and mentioned during research.